The Effect of Salinity Towards Resistivity for Groundwater Interpretation - Mohammad Hilmi, Nur Aimi Sufiana; Madun, Aziman (Recent Trends in Civil Engineering and Built Environment, 2022)
The groundwater exploration in Malaysia is used widely to meet the increasing demand for domestic, agricultural, and industrial purposes. The problems with groundwater exploration are seawater intrusion, where the mixture of freshwater and seawater occurred in groundwater aquifers. If this is not avoided, groundwater supplies of water become contaminated, necessitating additional treatment. The objectives of this research were to determine the effect of salinity concentration towards the resistivity value and determine the concentrations of saline solutions when the effect of soil particle sizes diminishes. The groundwater interpretation will be carried out through lab-based approaches and analytical instruments. The sodium chloride (NaCl) solutions will be the indicator of the saline solutions. The soil samples used in this experiment were sand and gravel samples. The method used for groundwater interpretation was through Electrical Resistivity Method using M.C Miller Resistivity Meter, 400A. The two-pinned electrodes are connected to the resistivity meter and the resistivity value acting upon the soil sample was observed. The resistivity value shows a negative relationship against the salt concentrations for the sand sample. However, for gravel sample shows the constant value for each salt concentration which proved on the second objective where the effect of soil particle size diminishes. The study found that the increasing number of salt content (NaCl) reduced the resistivity value because of the presence of ions and electrolytes which allows more conductivity. The study for groundwater interpretation where the saline water and freshwater interferes was necessary for groundwater supplies.